Potensi Pengembangan Ternak Sapi Potong Dalam Sektor Agribsinsis: Analisis Pengaruh Produksi Dan Harga Terhadap Pendapatan Peternak Di Kecamatan Perbaungan Kabupaten Serdang Bedagai - Alif Ramadhan; Fadhil Ardiansyah; Muhammad Ryan Harmawan; Asty Adelia; Egi Vatia; Kiagus M.Zain Basriwijaya (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study aims to assess the potential development of beef cattle farming businesses for farmers in Perbaungan District, Serdang Bedagai Regency. The variables used in this research are beef cattle production and beef cattle prices as independent variables, and farmers' income as the dependent variable. The analysis approach utilizes a quantitative method with a multiple linear regression model using time-series data sourced from the Central Statistics Agency (BPS) of Perbaungan District for the period 2019–2023. The results indicate that the development of beef cattle farming businesses in Perbaungan District has significant potential to increase farmers' income and improve their welfare. The variables of beef cattle production and beef cattle prices collectively have a significant influence on farmers' income.